Automated polymerase chain reaction in capillary tubes with hot air. - Wittwer, C T (1989)
We describe a simple, compact, inexpensive thermal cycler that can be used for the polymerase chain reaction. Based on heat transfer with air to samples in sealed capillary tubes, the apparatus resembles a recirculating hair dryer. The temperature is regulated via thermocouple input to a programmable set-point process controller that provides proportional output to a solid state relay controlling a heating coil. For efficient cooling after the denaturation step, the controller activates a solenoid that opens a door to vent hot air and allows cool air to enter. Temperature-time profiles and amplification results approximate those obtained using water baths and microfuge tubes.